Adobe Photoshop CS3 extended - Ferguson, Dwayne; Virtual Training Company ([Australia] : Virtual Training Company, 2008)
Professional illustrator and television animation art director, Dwayne Ferguson shows an in-depth look at the powerful application of Adobe Photoshop CS3 Extended such as import 3D models from popular application such as Maya, Lightwave and more to add rich textures and then return those images to our objects. Also import video and film to add special effects, rotoscoping, cloning and even traditional Photoshop filters
Title from container
Training CD
Contains 135 movies with total time 8.5 hours
See record from bib id 3424179 for payment details
System requirements: Mac: System 9 or higher ; PC: Windows 98 or higher, 32MB System RAM, 6MB Video RAM, 16x CD-ROM ; QuickTime 6
Keywords: Adobe Photoshop; Digital video; Computer animation